2013
DOI: 10.2147/ndt.s42714
|View full text |Cite
|
Sign up to set email alerts
|

Neuropsychology of eating disorders: 1995–2012

Abstract: Eating disorders are considered psychiatric pathologies that are characterized by pathological worry related to body shape and weight. The lack of progress in treatment development, at least in part, reflects the fact that little is known about the pathophysiologic mechanisms that account for the development and persistence of eating disorders. The possibility that patients with eating disorders have a dysfunction of the central nervous system has been previously explored; several studies assessing the relatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
31
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(39 citation statements)
references
References 90 publications
7
31
1
Order By: Relevance
“…In particular, a low score on the PT scale is indicative of an impairment in interpersonal functioning,4 and converges with the repeated findings of altered social skills in anorectic patients 6. Moreover, since executive functions contribute to the effective development of CE31 and, at the same time, are consistently reported as impaired in AN subjects,32 further research is warranted to clarify the possibility that executive functions deficits interfere with the reduced CE abilities of AN patients.…”
Section: Discussionsupporting
confidence: 72%
“…In particular, a low score on the PT scale is indicative of an impairment in interpersonal functioning,4 and converges with the repeated findings of altered social skills in anorectic patients 6. Moreover, since executive functions contribute to the effective development of CE31 and, at the same time, are consistently reported as impaired in AN subjects,32 further research is warranted to clarify the possibility that executive functions deficits interfere with the reduced CE abilities of AN patients.…”
Section: Discussionsupporting
confidence: 72%
“…This cognitive ability has been found to be altered with a high degree of consistency in adults with AN (Tchanturia et al, , 2012Galimberti et al, 2013; for a review see Jáuregui-Lobera (2013). Interestingly, our group demonstrated that adult AN patients are rigid not only in verbal but also in non-verbal domains, as recently confirmed (Pignatti and Bernasconi, 2013).…”
Section: Introductionsupporting
confidence: 71%
“…Overall, difficulties in executive functions (e.g., cognitive flexibility) and increased cognitive biases to disorder-related stimuli (i.e., attentional bias) were found in individuals with AN and BN. 8,9 Consistent with findings in individuals with AN and BN, systematic reviews identified deficits in overweight/obese individuals primarily in the domain of executive functions (e.g., difficulties in cognitive flexibility and decision making). 4 However, recent investigations did not consistently replicate difficulties in, for example, cognitive flexibility in individuals with AN and BN.…”
Section: Introductionsupporting
confidence: 55%
“…8 Thus, implications for future research include the development of guidelines and standard assessment batteries to assess various CoF aspects, for example, the Ravello Profile, 103 to identify specific difficulties across diagnoses or within patients with one diagnosis. 8 Thus, implications for future research include the development of guidelines and standard assessment batteries to assess various CoF aspects, for example, the Ravello Profile, 103 to identify specific difficulties across diagnoses or within patients with one diagnosis.…”
Section: Research Implicationsmentioning
confidence: 99%